Strategi Pemasaran Sekolah Dasar pada Masa Pandemi - Afridayani Afridayani (EkoPreneur, 2020)
The Covid-19 outbreak has had an impact on all activities, one of which is schools. The school is a non-profit educational institution engaged in educational services. In the current era of the COVID-19 pandemic, school competition is getting tougher, of course, schools must have the right strategy in marketing schools. The purpose of this study was to determine the marketing strategy carried out by the Integrated Islamic Elementary School (SDIT) Permata Gemilang (SDIT) for New Student Admissions (PPDB) for the 2021/2022 academic year. The type of research used is a qualitative approach with data collection techniques literature study. The research location is SDIT Permata Gemilang. Jl. Rawa Mekar Jaya Village, BSD, South Tangerang. In conclusion, in facing the challenges of changing times, education marketing is required to be more productive and actively respond to changes, including the process of changing marketing activities during the COVID-19 pandemic. School marketers must develop the right strategy to be implemented during this pandemic so that the marketing carried out by marketers can run well and maximally. Things that can be done by marketers include 1. Applying a marketing mix that is done online (online). In the application of this marketing mix, a marketer can apply 7 marketing elements, abbreviated as 7P, which includes the product, price, place, promotion, people, physical evidence, and process. Keywords: Marketing strategy, Marketing Mix